Effectiveness And Efficiency Of Gopay Usage Among Generation Z In Rural East Kalimantan - Purnamasari, Ike; Ariswati, Lusiana Desy; Chandika Mahendra Widaryo (Lembaga Teewan Journal Solutions, 2026)
This study evaluates the post-adoption effectiveness and efficiency of GoPay usage among Generation Z in Kutai Kartanegara and Kutai Barat Regencies, East Kalimantan, within the context of 2025 regional fiscal pressures and digital infrastructure limitations in rural settings. The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, non-participant observation, and documentation involving six Generation Z informants selected through purposive sampling. Data analysis was conducted phenomenologically using NVivo 15 software through textual description, structural description, and synthesis of meanings. The findings indicate that GoPay is perceived as highly effective and efficient due to its transaction speed, ease of use, security features, and promotional benefits that contribute to cost savings. TreeMap and WordCloud visualizations reveal the dominance of terms such as “fast,” “transaction,” “efficient,” and “time” in participants’ narratives. Beyond functioning as a digital payment tool, GoPay also serves as a simple financial management instrument through balance monitoring and transaction history features. However, challenges such as limited digital literacy and unstable internet connectivity remain significant barriers in rural contexts. This study recommends strengthening digital literacy programs and expanding digital infrastructure to optimize financial inclusion for Generation Z in East Kalimantan.